An Underwater Sensor Allocation Scheme for Noncircular Sensing Coverage Regions. (17th January 2013) - Golen, Erik F.; Lutzer, Carl V.; Ross, David S.; Shenoy, Nirmala
Abstract : Intelligently allocating underwater sensors to a large area of interest whose acoustic characteristics vary throughout is a challenge, especially for an area clearance scenario. In these scenarios, there is no apparent target for an adversary to gravitate towards, such as a ship or a port. Thus, it is difficult to determine how the field designer should allocate sensors so that their deployment locations can be planned efficiently. The previously proposed Game Theory Field Design (GTFD) model can achieve an intelligent sensor allocation, using a game theoretic approach, for sensors with circular coverage regions. In practice, however, the sensing coverage of an underwater sensor will likely be noncircular due to the azimuthally dependent bathymetric phenomena and other underwater irregularities. As a result, an extension of the model is proposed for allocating sensors for the irregularly shaped sensing coverage regions. This work provides two validations of the extended GTFD model. The first is an analytical comparison with sensing coverage regions whose shape is well understood, and the second uses simulation to validate the model for the irregularly shaped regions.